Intravenous paracetamol for neonates: long-term diseases not escalated during 5 years of follow-up. Issue 2 (17th September 2020) - Juujärvi, Sanna; Saarela, Timo; Pokka, Tytti; Hallman, Mikko; Aikio, Outi
Abstract : Objective: To evaluate the long-term adverse reactions of paracetamol in children who required intensive care shortly after birth. Paracetamol is a widely used analgesic in neonates, but the long-term studies are lacking. Previous epidemiological studies have reported associations between early paracetamol intake and diseases in childhood. Design: Five-year follow-up cohort of children who required intensive care shortly after birth. Setting: Single tertiary care hospital; neonatal and paediatric intensive care units. Interventions: Intravenous paracetamol was administered for pain and discomfort to the neonates during their intensive care, while for the control infants, it was not available. Main outcome measures: The primary outcome was the incidence of asthma; secondary outcomes were neonatal diseases and long-term morbidities (atopic dermatitis, inflammatory bowel disease, autism, speech disorders, cerebral palsy). Long-term morbidities were adjusted based on antenatal and neonatal risk factors. Results: We screened all neonates admitted to the intensive care units soon after birth in Oulu University Hospital, Oulu, Finland, during 1 October 2007 to 31 December 2013. Altogether, 1552 infants needed intensive care. Of them, 735 (47%) were treated with intravenous paracetamol. We obtained their long-term data from the Finnish National Institute for Health and Welfare, including all physician-made diagnoses from all primary healthcare units and hospitals in Finland. We found no difference in the asthma incidence or in other long-term morbidities between paracetamol-treated and non-exposed infants. Conclusions: Intravenous paracetamol given to neonates did not associate with childhood disorders compared with the non-exposed infants during the 5-year follow-up. The previous hypothesis that early paracetamol use causes childhood morbidities was not confirmed. Abstract : Paracetamol exposure in neonatal life (pain, discomfort) is not associated with childhood disorders (asthma, atopic dermatitis, inflammatory bowel disease, autism, speech disorders, cerebral palsy) when compared to non-exposed cases at the age of 5 years in one NICU.